Contracts in the Old Testament: A Form Critical Investigation - Tucker, Gene Milton
Ph.D.; University Microfilms Order No. 66-7259. Microfilm $3.00: Xerography $9.70; Dissertation Abstracts A: The Humanities and Social Sciences 27 (Ann Arbor, Mich. 1966) 530-A.